A cross-sectional study of USFDA warning letters issued for cGMP violations pertaining to medical devices - Kavyashree, Praveen Hiremath, Francis Fernandes, Pradeep Muragundi (Journal of Applied Pharmaceutical Science, 2020)
Most of the prior studies concentrated on warning letters issued for clinical investigation, Institutional review board, and infringement of promotional claims, no studies assessed the warning letters issued for infringements of Current Good Manufacturing Practice (cGMP) pertaining to medical devices. Hence, there is a need to carry out a cross-sectional study of these warning letters. Publically available U.S. Food & Drug Administration (USFDA) letters under the law of the freedom of Information Act sent to the pharmaceutical company were accessed from the USFDA website. A standard data collection tool (Excel Spreadsheet) with all letters of warning issued from January 2008 to July 2018 was developed. Letters have been manually screened. Warning letters related to medical device breaches of cGMP were screened based on the letter's subject and content. Overall, 669 warning letters issued for medical device cGMP violations were reviewed between January 2008 and November 2018. From 2008 to 2013, there was a downward trend in the issuance of warning letters. The number of warning letters issued in 2014 was 101, followed by 106 in 2015, as the USFDA focused more on data integrity issues, while the number decreased to 53, 27, and 19, respectively, in 2016, 2017, and 2018. The highest number of warning letters were issued to manufacturers located in the USA (379), followed by Canada (52), and China (37). Section 820.30 of Title 21 CFR was found to be most violated with 603 infringements. This section represents the design control requirements for cGMP. Class 2 type of medical devices were found to be most violated (82%), followed by Class 3 with 7%. Only 32% of the companies responded to the warning letters although 52% Not Issued the closeout letter followed by 16% of the letters were considered as non-applicable letters. With the time, scientific developments and increased awareness of both regulatory authorities and industries/ academic organizations, overall improvement are observed with significant decrease in the number of warning letters.
Keywords: USFDA, warning letters, medical devices, cGMP violations, data Integrity.